Energy Aware Optimal Resource Allocation in Backhaul Constraint Wireless Networks: A Two Base Stations Scenario. (16th August 2015) - Gao, Yuan; Xue, Peng; Li, Yi; Yu, Hongyi; Wang, Xianfeng; Gao, Shihai
In future wireless communication systems, the capacity constrained backhaul gradually becomes bottleneck both in spectrum efficiency and energy efficiency, especially in joint processing of LTE-Advanced. This paper addresses the issue of energy aware resource allocation with limited backhaul capacity in uplink cooperative reception, where two base stations (BSs) equipped with single-antenna each serving multiple users with single-antenna via multicarrier are considered. We propose a novel energy efficient cooperative scheme based on compress-and-forward and user pairing to solve the problem in two base stations scenario. In order to maximize system throughput and increase energy efficiency under the limited backhaul capacity constraint, we formulate the joint optimization problem of user pairing, subcarrier mapping, and backhaul capacity sharing between different pairs (subcarriers). An energy efficient algorithm based on alternating optimization strategy and perfect mapping is proposed to solve this mixed integer programming problem. Simulations show that this allocation algorithm can improve the system capacity and energy efficiency significantly compared with the blind alternatives.